PENGARUH UKURAN, UMUR PERUSAHAAN, STRUKTUR KEPEMILIKAN, DAN PROFITABILITAS PADA PENGUNGKAPAN WAJIB LAPORAN TAHUNAN - Maharani, Luh Gede Putri; Budiasih, I.G.A.N. (E-Jurnal Akuntansi; Vol 14 No 1 (2016), 2016)
Mandatory disclosure is the minimum disclosures of financial statements required by the applicable accounting standards. Mandatory disclosure of allegedly influenced by several factors such as firm size, firm age, ownership structure, and profitability. The purpose of this study is to determine the effect of firm size, firm age, ownership structure, and profitability on mandatory disclosure. Sampling method in this research was purposive sampling and acquired 39 observational data as the sample. The data used in this research was secondary data. The data analysis technique used was multiple linear regression using SPSS 17.0. The results showed that the age of the firm and positive effect on the ownership structure of mandatory disclosures, and the size of the company and profitability has no effect on mandatory disclosure.
Keywords: Firm Size, Firm Age, Ownership Structure, Profitability, Mandatory Disclosure